Early Immune Modulation in European Seabass (Dicentrarchus labrax) Juveniles in Response to Betanodavirus Infection - Mariana Vaz; Damiana Pires; Pedro Pires; Marco Simões; Ana Pombo; Paulo Santos; Beatriz do Carmo; Ricardo Passos; Janina Z. Costa; Kim D. Thompson; Teresa Baptista (Fishes, 2022)
The early host–pathogen interaction between European seabass (Dicentrarchus labrax) and Betanodavirus was examined by using juvenile fish infected intramuscularly with RGNNV (red-spotted grouper nervous necrosis virus). The time course selected for sampling (0–144 h post-infection (hpi)) covered the early stages of infection, with hematological, antioxidant and immunological responses examined. Early activation of the host’s immune system was seen in the first few hours post-infection (6 to 9 hpi), as evidenced by an increase in tnfα, cd28 and c3 expression in the head kidney of infected fish. Most hematological parameters that were examined showed significant differences between sampling times, including differences in the number of thrombocytes and various leukocyte populations. The plasma lysozyme concentration decreased significantly over the course of the trial, and most antioxidant parameters examined in the liver showed significant differences over the infection period. At 144 hpi, peak expression of tnfα and il-1β coincided with the appearance of disease symptoms, peak levels of virus in the brain and high levels of fish mortality. The results of the study show the importance of analyzing the early interactions between European seabass and Betanodavirus to establish early indicators of infection to prevent more severe outcomes of the infection from occurring.